A study of teambuilding practices: a case study at Academic Affairs Department in MARA University of Technology and work department in Alor Gajah - Abu Bakar, Dahlan Ismail (2004)
Nowadays, many organizations have introduced or apply work team approach in completing their task and achieving their organization’s goals. It is important for organization to have best and effective teamwork. Many organizations are looking into having effective and efficient employees in completing and achieving organization’s goals. This is due to be competitive and competence in the global world. The practice of teambuilding is popular among private sectors and little be known in the public sectors. A sample of 40 employees was given the questionnaires. The studies try to find the practices of teambuilding at public organization. Instead of self-administered questionnaires, other methods of research that have been used in this study are data collection and Statical Package for Social Science (SPSS). The finding is hopefully can contribute and help this department in order to increasing employees work performance at the workplace.